3
$\begingroup$

Let $f,g$ and $h$ be polynomials. Show that $\gcd(f,g,h)=\gcd(\gcd(f,g),h)$.

I was thinking of signing $\gcd(f,g)=d$ and then write it by using Euclid's algorithm, but I couldn't get anything proper.

$\endgroup$
2
$\begingroup$

Can you show something along the following lines?

If $p$ is a polynomial that divides all of $f$, $g$ and $h$, will it also divide $\gcd(f,g)$ and $h$?

And vice versa, if $q$ is a polynomial that divides both $\gcd(f,g)$ and $h$, will it divide $f$, $g$, and $h$?

$\endgroup$
0
$\begingroup$

The proof of the associativity property of gcd follows immediately from the following

$\rm\qquad\quad\ \ \ d\mid (a,b,\ldots) \color{#c00}\iff d\mid a,b,\ldots\quad $ [Universal Property of GCD]

Hence $\rm\,\ \ d\mid((a,b),c)\color{#c00}\iff d\mid (a,b),\, c\color{#c00}\iff d\mid a,b,c $

Thus the associativity of GCD boils down to the associativity of AND (which is implicit in above, i.e. $\rm\ d\mid a,\,b,\ldots\,$ means $\rm\,d\mid a\,$ AND $\rm\,d\mid b,\ldots\,).$


Compare analogous universal properties for more ell-known operations, e.g.

$\rm\qquad\quad\ \ \ S \supset A\cup B\color{#0a0}\iff S\supset A,B\quad $ [Universal Property of Union]

Hence $\rm\ \ \ S \supset (A\cup B)\cup C\color{#0a0}\iff S\supset A\cup B, C\color{#0a0}\iff S\supset A,B,C$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.